The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/feduc.2021.651908
|View full text |Cite
|
Sign up to set email alerts
|

Swedish Youths as Listeners of Global Englishes Speakers With Diverse Accents: Listener Intelligibility, Listener Comprehensibility, Accentedness Perception, and Accentedness Acceptance

Abstract: As reflected in the concept of Global Englishes, English mediates global communication, where English speakers represent not merely those from English-speaking countries like United Kingdom or United States but also global people from a wide range of linguistic backgrounds, who speak the language with diverse accents. Thus, to communicate internationally, cultivating a maximized listening proficiency for and positive attitudes toward global Englishes speakers with diverse accents is ever more important. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…White instructors are often expected to perform their Whiteness in such contexts. However, in alignment with Global Englishes principles, contemporary English learners must engage with a global community of diverse language users, cultures, and races (Jeong et al, 2021). Therefore, instructional methods should equip learners with the skills and awareness necessary for effective communication in diverse contexts (Rose and Galloway, 2019).…”
Section: Global Englishes Language Teaching Framework For Anti-racist...mentioning
confidence: 99%
“…White instructors are often expected to perform their Whiteness in such contexts. However, in alignment with Global Englishes principles, contemporary English learners must engage with a global community of diverse language users, cultures, and races (Jeong et al, 2021). Therefore, instructional methods should equip learners with the skills and awareness necessary for effective communication in diverse contexts (Rose and Galloway, 2019).…”
Section: Global Englishes Language Teaching Framework For Anti-racist...mentioning
confidence: 99%
“…As noted by Lindemann in her US context (discussed below), helping students become good listeners of diverse English accents requires not only training listening skills and strategies but also critically addressing attitudes towards different accents (Lindemann, 2002;. Through their education (Forsberg, Jansen & Mohr, 2019) and exposure to the popular culture of English-speaking countries, especially American pop culture, young Swedes tend to have positive attitudes towards privileged native accents and somewhat negative ones towards other English accents (Eriksson, 2019;Jeong et al, 2021), which Jeong thought should be addressed in her phonetics courses. When time allows, she organizes asynchronous written discussions on online learning platforms for critically reflecting on attitudes towards different English accents.…”
Section: How Teaching and Learning Has Proceededmentioning
confidence: 99%
“…One approach to resisting standard language ideology and native speakerism, although not exactly within the fields of phonetics and phonology, investigates the possibility of training native English listeners to better understand diverse international speakers (e.g., Kubota, 2001;Lindemann, Campbell, Litzenberg, & Subtirelu, 2016). The idea of training native speakers to be better listeners of diverse accents is not only powerful for dismantling standard language ideology and native speakerism, but has also led to the revelation that, for using English for global communication, non-native speakers-as well as native speakers-need to train their listening skills for diverse English pronunciations (Jeong, Elgemark, & Thorén, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another research about the effect of non-native and native language backgrounds on intelligibility perceived by many different native language backgrounds was conducted by Jeong et al (2021). The result showed that English and American native speakers were the most intelligible to Swedish listeners.…”
Section: Introductionmentioning
confidence: 99%